Effectiveness of rotavirus vaccines against rotavirus infection and hospitalization in Latin America: systematic review and meta-analysis. Issue 1 (December 2016) - Santos, Victor; Marques, Daniella; Martins-Filho, Paulo; Cuevas, Luis; Gurgel, Ricardo
Abstract Background Rotavirus was the leading cause of childhood diarrhoea-related hospitalisations and death before the introduction of rotavirus vaccines. Methods We describe the effectiveness of rotavirus vaccines to prevent rotavirus infections and hospitalizations and the main rotavirus strains circulating before and after vaccine introduction through a systematic review and meta-analysis of studies published between 1990 and 2014. 203 studies were included to estimate the proportion of infections due to rotavirus and 10 to assess the impact of the vaccines. 41 of 46 studies in the post-vaccination period were used for meta-analysis of genotypes, 20 to calculate VE against infection, eight for VE against hospitalisation and seven for VE against severe rotavirus-diarrhoea. Results 24.3 % (95 %CI 22.1–26.5) and 16.1 % (95 %CI 13.2–19.3) of cases of diarrhoea were due to rotavirus before and after vaccine introduction, respectively. The most prevalent G types after vaccine introduction were G2 (51.6 %, 95 %CI 38–65), G9 (14.5 %, 95 %CI 7–23) and G1 (14.2 %, 95 %CI 7–23); while the most prevalent P types were P[4] (54.1 %, 95 %CI 41–67) and P[8] (33 %, 95 %CI 22–46). G2P[4] was the most frequent genotype combination after vaccine introduction. Effectiveness was 53 % (95 %CI 46–60) against infection, 73 % (95 %CI, 66–78) against hospitalisation and 74 % (95 %CI, 68.0–78.0) against severe diarrhoea. Reductions in hospitalisations and mortality due to diarrhoea were observed in countries that adopted universal rotavirus vaccination. Conclusions Rotavirus vaccines are effective in preventing rotavirus-diarrhoea in children in Latin America. The vaccines were associated with changes in genotype distribution.